Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.